The use of virtual communities of practice to improve interprofessional collaboration and education: findings from an integrated review. Issue 2 (4th March 2018) - McLoughlin, Clodagh; Patel, Kunal D; O'Callaghan, Tom; Reeves, Scott
ABSTRACT: The recent growth in online technology has led to a rapid increase in the sharing of health related information globally. Health and social care professionals are now using a wide range of virtual communities of practice (VCoPs) for learning, support, continuing professional education, knowledge management and information sharing. In this article, we report the findings from a review of the literature that explored the use of VCoPs by health and social care professionals to determine their potential for interprofessional education and collaboration. We employed integrated review methods to search and identify relevant VCoP articles. We undertook searches of PubMed and Google Scholar from 2000, which after screening, resulted in the inclusion of 19 articles. A thematic analysis generated the following key issues related to the use of VCoPs: 'definitions and approaches', 'technological infrastructure', 'reported benefits', 'participation issues', 'trust and privacy and 'technical ability'. Based on the findings from this review, there is some evidence that VCoPs can offer an informal method of professional and interprofessional development for clinicians, and can decrease social and professional isolation. However, for VCoPs to be successful, issues of privacy, trust, encouragement and technology need to be addressed.